Tourism and poverty reduction: Empirical evidence from China. Issue 2 (March 2020) - Zhao, Lei; Xia, Xin
This study empirically examines whether tourism affects poverty reduction based on the panel data of Chinese provinces for the period from 1999 to 2014. Using more comprehensive Foster–Greer–Thorbecke index to decompose poverty into three indices, namely, headcount ratio, poverty gap, and poverty severity, we investigate the relationship between tourism and poverty indices within a single framework. The empirical analysis indicates that tourism has a positive effect on poverty reduction and the concomitant inequality in the distribution of income among the poor could weaken the poverty reduction effect of tourism. China's western provinces confirm a stronger relationship between tourism and poverty reduction, although the effect of tourism on poverty in the eastern provinces is nearly negligible. We also identify possible mechanisms by which tourism may have an impact on poverty. The results provide empirical evidence to provide an improved assessment of the pro-poor effect of tourism in China.